Optimization of bread production with linear programming method (case study : CV. Roti Ca) - Nur' Aini; Emy Khikmawati; M W Wardana (Jurnal Rekayasa Industri (JRI), 2022)
Optimal production is the main goal in a business, which is to achieve maximum profit. CV. Roti Ca is a company engaged in food products. CV. Roti Ca was established since 2011 producing sandwiches and flatbreads with chocolate and green bean flavors. This study aims to determine the optimal combination of products so as to get maximum results using linear programming. The method used in this study is linear programming which can be applied to produce bread with a simplex model in order to obtain the optimum solution so that profits can be achieved. The results showed that the optimal sales obtained by the factory was Rp. 2,084,568,000, and the number of breads that can be produced each month is 2,605,711 pcs with ca 1,185679 pcs of chocolate sandwiches, ca 306,913 pcs of chocolate flatbread and 1.131,119 pcs of green bean flatbread.Â Keywords: Linear Programming Method, Simplex Method, Optimization, Bread, Qm For Windows